Occult H. pylori infection partially explains 'false-positive' results of 13C-urea breath test. Issue 5 (October 2015) - Ramírez-Lázaro, María J; Lario, Sergio; Calvet, Xavier; Sánchez-Delgado, Jordi; Montserrat, Antònia; Quílez, Elisa M; Casalots, Alex; Suarez, David; Campo, Rafel; Brullet, Enric; Junquera, Félix; Sanfeliu, Isabel; et al.
Background: In a previous study, UBiT-100 mg, (Otsuka, Spain), a commercial 13 C-urea breath test omitting citric acid pre-treatment, had a high rate of false-positive results; however, it is possible that UBiT detected low-density 'occult' infection missed by other routine reference tests. We aimed to validate previous results in a new cohort and to rule out the possibility that false-positive UBiT were due to an 'occult' infection missed by reference tests. Methods: Dyspeptic patients ( n = 272) were prospectively enrolled and UBiT was performed, according to the manufacturer's recommendations. Helicobacter pylori infection was determined by combining culture, histology and rapid urease test results. We calculated UBiT sensitivity, specificity, positive and negative predictive values (with 95% CI). In addition, we evaluated 'occult' H. pylori infection using two previously-validated polymerase chain reaction (PCR) methods for urease A (UreA) and 16 S sequences in gastric biopsies. We included 44 patients with a false-positive UBiT, and two control groups of 25 patients each, that were positive and negative for all H. pylori tests. Results: UBiT showed a false-positive rate of 17%, with a specificity of 83%. All the positive controls and 12 of 44 patients (27%) with false-positive UBiT were positive for all two PCR tests; by contrast, none of our negative controls had two positive PCR tests. Conclusions: UBiT suffers from a high rate of false-positive results and sub-optimal specificity, and the protocol skipping citric acid pre-treatment should be revised; however, low-density 'occult' H. pylori infection that was undetectable by conventional tests accounted for around 25% of the 'false-positive' results.